Hepatic changes in abortions and infants from HIV-positive mothers - Oliveira, Paula Ferraz de; Nascimento, Gustavo Henrique; Weide, Luciene de Carvalho Cardoso; Xavier, Analúcia Rampazzo; Kanaan, Salim; Lopes, Vânia Glória Silami (Brazilian Journal of Sexually Transmitted Diseases, 2013)
Introduction: There are a few works in the literature concerning pathological and anatomical alterations of hepatic lesions in necropsies of aborts, stillbirths and children from HIV-positive mothers. Objective: To report pathological and anathomical hepatic alterations in fetus and infants from HIV-positive mothers, correlating them with HIV infections, etiologic agents of opportunistic infections and drugs used in different treatments. Methods: necropsy material from 15 children and 5 aborts was obtained from the Department of Pathology, Hospital Universitário Antônio Pedro, Fluminense Federal University, from 1986 to 2007. Aborts, stillbirths and children definitions followed World Health Organization criteria. Macro- and microscopic studies were performed after parafin inclusion with hematoxilin-eosin and other methods (periodic acid-Shiff, reticulin, Gomory’s trichrome, silver methenamine, and Sudan stains). All necropsies were completed. Results: Results showed macroscopic changes in 13 cases, at least in one category, and microscopic changes compatible with esteatosis in 12 cases, necrosis in 7 cases, and colestasis in 4 children and stillbirths. Out of five abortions, two were due to mothers using zidovudina. All patients showed opportunistic infection. Conclusion: Macroscopic and microscopic hepatic changes are important in these patients and may not be related to the high frequency of the opportunistic infections. This study will provide subsidies for understanding the pathogenesis of hepatic problems caused by HIV virus, opportunistic agents and drugs used in therapy